Fermented cottonseed and rapeseed meals outperform soybean meal in improving performance, rumen fermentation, and bacterial composition in Hu sheep - Rehemujiang, Halidai; Yusuf, Hassan Ali; Ma, Tao; Diao, QiYu; Kong, Luxin; Kang, Lingyun; Tu, Yan (Frontiers in Microbiology, 2023)
Background: In this study was to evaluate the effects of replacing soybean meal (SBM) with cottonseed meal (CSM) or rapeseed meal (RSM) on the growth performance, rumen fermentation, and bacterial composision of Hu sheep. Fifty-one four-month-old indigenous male Hu sheep with 22.51 ± 2.84 kg initial body weight and similar backgrounds were randomly allocated to three treatments:1) non-fermented total mixed ration (TMR) with SBM (CK), 2) fermented TMR containing CSM (F-CSM group), and 3) fermented TMR containing RSM (F-RSM group). Results: Dry matter intake was significantly different (P < 0.05) among the three groups. The F-RSM group had a significantly higher average daily gain than the CK and F-CSM groups (P < 0.05). The rumen pH of the CK group was significantly lower than that of the F-CSM and F-RSM groups (P < 0.05), and the volatile fatty acid (VFA) concentrations the F-CSM group having higher concentrations than the F-RSM and CK groups. Microbial crude protein yield was significantly higher in the F-CSM and F-RSM groups than in the CK group (P < 0.05). The pepsin and cellulose enzyme activities in the F-CSM group were significantly higher than those in the F-RSM group (P < 0.05). The relative abundance of Bacteroidetes in the CK and F-RSM groups was higher (P < 0.05) than that in the F-CSM group. The relative abundance of Firmicutes was lower in the CK group than in the other groups (P < 0.05). The relative abundance of Prevotella in the F-CSM and F-RSM groups was higher than that in the CK group (P < 0.05). The relative abundances of Veillonellaceae_UCG-001 and Lachnospiraceae_XPB1014 correlated with rumen butyric acid content and NH3-N content (P < 0.05). Gene function prediction revealed that replacing SBM with F-CSM or F-RSM in the diet of Hu sheep can promote glycan biosynthesis and metabolism. Conclusion: The substitution of SBM with F-CSM and F-RSM could affect the richness and diversity of rumen bacteria at the phylum and genus levels. Replacement of SBM with F-CSM increased VFA yield and further promoted the performance of Hu sheep.